2019
DOI: 10.3389/fphys.2019.00441
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of Respiratory-Related Postural Perturbation Is Achieved by Maintenance of Head-to-Pelvis Alignment in Healthy Humans

Abstract: The maintenance of upright balance in healthy humans requires the preservation of a horizontal gaze, best achieved through dynamical adjustments of spinal curvatures and a pelvic tilt that keeps the head-to-pelvis alignment close to vertical. It is currently unknown whether the spinal and pelvic compensations of respiratory-related postural perturbations are associated with preservation of the head-to-pelvis vertical alignment. We tested this hypothesis by comparing postural alignment variables at extreme lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…Indeed, we did not observed in our patients any pelvic compensation (29). Conversely we observed a compensatory thoracic hyperkyphosis (24,29). This compensation probably limits the disturbance of balance secondary to pathological spinal alignment (35), but may increase the risk of falls and others hyperkyphosisrelated comorbidities (46).…”
Section: Upper Airways and Spinal Alignment In Osascontrasting
confidence: 42%
See 3 more Smart Citations
“…Indeed, we did not observed in our patients any pelvic compensation (29). Conversely we observed a compensatory thoracic hyperkyphosis (24,29). This compensation probably limits the disturbance of balance secondary to pathological spinal alignment (35), but may increase the risk of falls and others hyperkyphosisrelated comorbidities (46).…”
Section: Upper Airways and Spinal Alignment In Osascontrasting
confidence: 42%
“…Anatomically, both rely on the integrity of the same musculoskeletal structures: the spine, thoracic cage, and trunk musculature. It has been shown that spinal curvatures are severely constrained by extreme variations in pulmonary volume (24). Additionally, normal ventilation cyclically perturbs balance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postural and respiratory dynamics are intimately linked and exhibit strong temporal relationships in healthy humans (Dally 1908;Gurfinkel et al 1971;Perry and Carrier 2006). Ribcage movements during breathing disturb an individual's balance by modifying the costo-vertebral articulation position, thoracic spinal curvature and postural alignment (Dally 1908;Attali et al 2019) and by inducing ribcagerelated centre of mass (CoM) displacements. Breathingrelated postural perturbations during natural breathing are partially counteracted by phasic contractions of paravertebral (Kantor et al 2001) and pelvic floor muscles (Hodges et al 2007;Talasz et al 2011).…”
Section: Introductionmentioning
confidence: 99%